2019
DOI: 10.21638/spbu11.2019.202
|View full text |Cite
|
Sign up to set email alerts
|

Problems of diagnostics and treatment of diffuse — toxic goiter (Graves’ disease)

Abstract: The article is devoted to prevalence, contemporary diagnostic methods and treatment of Grave’s disease. Advantages and disadvantages of different treatment options are discussed. The cause of the disease can be environmental conditions, infectious diseases, severe operational intervention, drugs, trauma, especially brain traumas, iodine deficiency and radiation damage of thyroid in iodine deficiency conditions, familial predisposition. The ideal treatment of Graves’ disease should ensure a fairly rapid elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…According to Ismailov & Khayitboyeva, 2019) and Kh, (2019), this fact justifies a higher incidence of iatrogenic injury to the parathyroid glands. In addition, parathyroid vessels may be compromised by the autoimmune process of diffuse toxic goiter (Ismailov & Khayitboyeva, 2019;Kh, 2019).…”
Section: Hyperthyroidism and Hypothyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ismailov & Khayitboyeva, 2019) and Kh, (2019), this fact justifies a higher incidence of iatrogenic injury to the parathyroid glands. In addition, parathyroid vessels may be compromised by the autoimmune process of diffuse toxic goiter (Ismailov & Khayitboyeva, 2019;Kh, 2019).…”
Section: Hyperthyroidism and Hypothyroidismmentioning
confidence: 99%
“…According to Ismailov & Khayitboyeva, 2019) and Kh, (2019), this fact justifies a higher incidence of iatrogenic injury to the parathyroid glands. In addition, parathyroid vessels may be compromised by the autoimmune process of diffuse toxic goiter (Ismailov & Khayitboyeva, 2019;Kh, 2019). Sakr, (2022) showed that the incidence of postoperative hypocalcemia was significantly higher in women with diffuse toxic goiter (Mahmoud F Sakr, 2022e).…”
Section: Hyperthyroidism and Hypothyroidismmentioning
confidence: 99%
“…), так и опасные для жизни (агранулоцитоз, гепатотоксичность и др.). Риск развития осложнений при приеме тиреостатиков является дозозависимым, токсичность в случае приема метимазола, карбимазола (в РФ не зарегистрирован) и пропилтиоурацила чаще всего перекрестная [5][6][7].…”
Section: Introductionunclassified